Propagation of short, nonlinear, second-sound pulses through He-II in one- and three-dimensional geometry - Efimov, V.B.; Kolmakov, G.V.; Kuliev, A.S.; Mezhov-Deglin, L.P. (Физика низких температур, 1998)
The results or an experimental study ot the evolution ot the shape ot nonlinear second-sound pulses in superfluid He-II are reported The pulses propagate in the bulk (3D geometry) and along a
cryoacoustic waveguide tilled with liquid helium (quasi-ID geometry) at temperatures corresponding to
the negative, positive, or zero nonlinearity coefficient. A strong dependence of the shape of the
propagating pulse on the dimensionality of the wave was observed. The finite size of the heater
(generator ot a sound) affects the profile ot a short 3D pulse even at distances many times greater than
the heater size, which restricts the minimal width of the excited pulse. The experimental data are
compared with the results of numerical simulations.